Utilization of banana waste biochar to reduce heavy metal contamination in soil and maize plants - Wedayani, Ni Made; Rai, I Nyoman; Mahardika, I Gede; Wijana, I Made Sara (Journal of Degraded and Mining Lands Management, 2024)
There are indications of heavy metal contamination in soil and agricultural products on paddy fields in Subak Kerdung, Bali. Soil amendments are needed to reduce heavy metal content in contaminated soil to minimize heavy metals in plants. Biochar that contains high organic carbon material and is highly resistant to decomposition is claimed to inhibit and reduce the content of heavy metals in soil and plants. Banana wastes containing cellulose and lignin are considered good as biochar raw materials. This research that aimed to observe the ability of banana waste biochar to reduce heavy metals in soil taken from Subak Kerdung, Bali, was conducted in a greenhouse using maize plants as control plants. The treatments tested consisted of two factors. The first factor was the type of banana waste as biochar-making material consisting of banana stem biochar, banana peel biochar, banana fruit bunch biochar, and mixed biochar (banana stem + banana peel + banana fruit bunch). The second factor was the biochar dosage, which consists of four contents, namely 0 t/ha, 5 t/ha, 10 t/ha, and 15 t/ha. All treatment combinations were arranged in a two-factor, randomized block design with three replications. The results showed that mixed biochar (banana stem + banana peel + banana fruit bunch) effectively reduced Pb and Cu in maize plants. In contrast, banana peel biochar could optimally reduce Cd content in soil and its content in plants. Based on the dose, 15 t/ha of mixed biochar reduced Pb and Cd contents, while 10 t/ha of mixed biochar reduced Cu content.